Factors Influencing Organizational Resilience: Mediating Roles of Adaptive Culture and Learning: Faktor-Faktor yang Mempengaruhi Ketahanan Organisasi: Peran Perantara Budaya Adaptif dan Pembelajaran - Esther Agustina; Alden Nelson; Agustinus Setyawan (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
Digital Business Transformation is a crucial adaptation for organizations to remain competitive in the digital age. It involves leveraging digital tools and technologies to alter operations, customer interactions, and value delivery. This analysis aims to investigate the impact of digital business on organizational resilience, exploring the interplay between digital transformation, adaptive culture, frugal innovation, organizational learning, and organizational resilience. In order to investigate casual linkages, this study takes a quantitative method and gathers data using questionnaires, with a sample size of 295 respondents in a range of jobs within contracting organizations, the study focusses on contractors in Indonesia. This analysis result showing that the digital business transformation can enhance the organizational resilience by improving creativity, efficiency and the agility. Beside this, digital transformation also can boost all the job productivity with the frugal innovation which this can helping organization for adapting from sudden shocks of market volatility.  With the digital business transformation, a company can have the adaptive culture for the organizational resilience on the responding for internal and external changes where the company will have better anticipate further changes. Furthermore, digital transformation can facilitate cost-effective solutions and strategic planning for dealing with challenges for a company.